Efficient Light‐Emitting Diodes via Hydrogen Bonding Induced Phase Modulation in Quasi‐2D Perovskites. Issue 21 (28th July 2022) - Zhuang, Lyuchao; Wei, Qi; Li, Chuanzhao; Ren, Hui; Li, Yanyong; Shi, Fangyi; Zhai, Lingling; Leng, Kai; Li, Mingjie; Lau, Shu Ping
Abstract: Quasi‐2D perovskites have drawn considerable attention in light‐emitting diodes due to their tunable energy landscape, efficient luminescence, and structural diversity. However, the excessive formation of low‐ n ( n ≤ 2) phases leads to lower carrier injection efficiency arising from the large injection barrier. Meanwhile, inefficient energy transfer caused by undesirable phases distribution results in multipeak emission. In this study, polar anti‐solvent is used that can interact with spacer cations via strong hydrogen bonding, tailoring phases distribution to address the issue. The ethyl acetate treatment induces preferential growth of large‐ n phases and enhances energy transfer due to the strong hydrogen bonding energy ≈ −17 kcal mol −1 . Leveraging these insights, efficient sky‐blue and green perovskite light‐emitting diodes are developed with improved external quantum efficiency ranging from 4.21% to 8.77%. The anti‐solvent treatment can open up a new avenue to regulate the phase distribution for an efficient energy funnel effect. Abstract : The low‐ n phases are commonly formed in solution‐processed quasi‐2D perovskite films due to the low formation energy, leading to the inefficient energy transfer. Anti‐solvent treatment induced hydrogen bonding with organic spacer cations can modulate the crystallization kinetics and lead to PbBr6 4‐ cluster stacking growth.